2016
DOI: 10.1093/pm/pnw251
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Use of Prescription Drug Monitoring Programs in Clinical Practice and Decision-Making: Table 1

Abstract: Greater consistency is needed in use of PDMP in monitoring existing patients and in conformity to guidelines against discharging patients from practice. Research is needed to determine optimal approaches to interpreting PDMP profiles in relation to clinical judgment, patient screeners, and other information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…the Washington Department of Health (DOH) PDMP operations manager. 18,[22][23][24][25][26][27] The survey instrument was pretested with 8 pharmacists with different backgrounds and experience to ensure validity and clarity on questions, response choice, and length. On the basis of pilot feedback, the survey underwent minor modifications.…”
Section: Resultsmentioning
confidence: 99%
“…the Washington Department of Health (DOH) PDMP operations manager. 18,[22][23][24][25][26][27] The survey instrument was pretested with 8 pharmacists with different backgrounds and experience to ensure validity and clarity on questions, response choice, and length. On the basis of pilot feedback, the survey underwent minor modifications.…”
Section: Resultsmentioning
confidence: 99%
“…In a survey of Texas community pharmacists, it was found that patients paying for controlled substances with cash or obtaining early refills were the most influential triggers for PMP use (Fleming et al, 2014). Several studies related similar findings where providers reported accessing the PMP when they were suspicious of the patient's drugseeking behavior (Hildebran et al, 2014; Irvine et al, 2014; Leichtling et al, 2017). Our study found that health care providers rated patients' misuse as the most important reason to consult with the PMP.…”
Section: Influence Of Vignette Variablesmentioning
confidence: 91%
“…Prescribers are left to grapple with the long-standing issue of BDZ dependence on a case-by-case basis, and this environment has unmasked tensions between patient stigma and the prescribers' duty of care [83]. More specifically, when required to manage a potentially inappropriate prescription, prescribers' decision-making is often guided by the patient-prescriber relationship [84], meaning they may decide to cease a prescription if they doubt a patients' intention, or if they had a prior negative experience with the patient. This is not surprising given the lack of guidance on managing competing needs of a patient dependent or "misusing" BDZs, and a prescriber held to account for dispensing a medication flagged as inappropriate by a PMP.…”
Section: The Prescriber's Dilemmamentioning
confidence: 99%